Methane hydrate recycling offshore of Mauritania probably after the last glacial maximum. (June 2017) - Li, Ang; Davies, Richard J.; Mathias, Simon
Abstract: To what extent methane liberated from marine hydrate will enter the ocean during a warmer world is unknown. Although methane release due to hydrate dissociation has been modelled, it is unclear whether or not methane will reach the seafloor during a warmer world and therefore contribute to oceanic and atmospheric budgets. Here we show, using a new three-dimensional (3-D) seismic dataset, that some hydrate deposits surround the gas chimneys passing through the HSZ. Bottom water warming since the last glacial maximum (LGM) is interpreted to cause hydrate dissociation but critically some of the released methane was not vented to the ocean. The released gas caused seal failure and free gas entered the hydrate stability zone (HSZ) through vertical gas chimneys to where new hydrate accumulations formed. This process is a new evidence for methane recycling and could account in part for the lack of methane in ice core records that cover warming events during the late Quaternary. This research provides new insight into how methane could be recycled rather than vented during a warmer world. Highlights: Hydrate deposits around gas chimneys are imaged using three-dimensional seismic data offshore Mauritania. Methane released from hydrate due to bottom water warming after the last glacial maximum was recycled rather than vented. This recycling could operate during a warmer world. It could, in part, explain the lack of methane in the ice records in the late Quaternary.